The social and cultural criticism of Al-e-Ahmad and Manfaluti in relation to women issues - Masoumeh Nemati Ghazvini; Narges Ansari (زن در فرهنگ و هنر, 2015)
Nowadays, because of the special and pivotal place of women in the family and nurturing future generations; problems and issues related to women has become one of the main concerns of thinkers and intellectuals. Jalal Al-e-Ahmad (1302-1348 AHS) and Mustafa Lutfi al-Manfaluti (1876-1924 AD) are two of the social reformers and contemporary writers in the field of Persian and Arabic literature. Each of them has presented women issues and criticized its different aspects as the conditions of their own society and the specific viewpoint that they had toward social and cultural problems. The present study which has compared the works of these two writers with a descriptive-analytic method indicate the presence of many similarities in their approach to women issues which can be studied in six general areas including west oxification, freedom, social injustices, hijab, marriage, and science learning and while being similar in concepts they are presented in somewhat different writing styles when appropriate.